(untitled) (Research, Society and Development, 2024)
Introduction: Diabetic Neuropathy (DN) is a complication of Type 2 Diabetes Mellitus (T2DM) commonly associated with vitamin B12 deficiency, especially in metformin users. Vitamin B12 supplementation may alleviate neuropathic symptoms, but its effectiveness and impact on glycemic control are still uncertain. Objective: To evaluate the effectiveness of vitamin B12 in treating DN in T2DM patients, focusing on symptom reduction, quality of life improvement, and glycemic control, particularly in metformin users. Methodology: This study is an integrative literature review investigating the effectiveness of vitamin B12 in treating DN. The research accessed the Biblioteca Virtual em Saúde and PubMed databases, using descriptors such as "Vitamin B12" and "Diabetic Neuropathy." Results: A total of 21 articles were found between 2019 and 2024, with 19 included in the final sample (18 in English and 1 in German). Most articles were published in 2020. The studies included 37% systematic reviews or meta-analyses and 16% randomized clinical trials. Discussion: DN leads to severe symptoms, such as diabetic foot. Glycemic control is crucial but challenging due to limited long-term efficacy. Metformin can cause vitamin B12 deficiency in about 30% of patients after 4 years, and vitamin B12 supplementation may help alleviate neuropathic symptoms. Conclusion: Vitamin B12 may reduce DN symptoms and improve nerve function. Further studies are needed to determine the optimal dosage, treatment duration, and potential adverse effects.